PENGARUH DISIPLIN BELAJAR TERHADAP PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP AL-AZHAR MANDIRI PALU - Fatima, Siti; Rustina; Patanggu, Irawan Hadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was carried out to examine the effect of students’ learning discipline on their academic achievement in Islamic Religious Education at SMP Al-Azhar Mandiri Palu. This study uses a quantitative survey approach with a comparative causal design. The population included 187 eighth-grade students, while 65 participants were chosen as the sample using probability sampling through the Slovin formula with a 10% error tolerance. Data were obtained through observation and questionnaires. The analysis techniques consisted of descriptive statistics and inferential statistics, including regression analysis followed by a t-test. The data processing was supported by SPSS version 26 for Windows. The results indicated that learning discipline (X) has a significantinfluence on learning achievement (Y). This is supported by statistical evidence showing that the t-value is higher than the t-table value (2,234 > 1,998), with a significance value of 0.029 < 0.05. Moreover, the R-square value of 0.073 shows that learning discipline contributes 7,3% to students’ achievement.